Tolerogenic and Activatory Plasmacytoid Dendritic Cells in Autoimmunity - Guery, Leslie; Hugues, Stephanie (Frontiers in Immunology, 2013)
Plasmacytoid dendritic cells (pDCs) are a particular subset of DCs that link innate and adaptive immunity. They are responsible for the substantial production of type 1 interferon (IFN-I) in response to viral RNA or DNA through activation of TLR7 and 9. Furthermore, pDCs present antigens (Ag) and induce naïve T cell differentiation. It has been demonstrated that pDCs can induce immunogenic T cell responses through differentiation of cytotoxic CD8+ T cells and effector CD4+ T cells. Conversely, pDCs exhibit strong tolerogenic functions by inducing CD8+ T cell deletion, CD4+ T cell anergy, and Treg differentiation. However, since IFN-I produced by pDCs efficiently activates and recruits conventional DCs, B cells, T cells, and NK cells, pDCs also indirectly affect the nature and the amplitude of adaptive immune responses. As a consequence, the precise role of Ag-presenting functions of pDCs in adaptive immunity has been difficult to dissect in vivo. Additionally, different experimental procedures led to conflicting results regarding the outcome of T cell responses induced by pDCs. During the development of autoimmunity, pDCs have been shown to play both immunogenic and tolerogenic functions depending on disease, disease progression, and the experimental conditions. In this review, we will discuss the relative contribution of innate and adaptive pDC functions in modulating T cell responses, particularly during the development of autoimmunity.